Movie in Classroom: Effect of Implementation in EFL Setting - Witri, I Luh Tika Sulesa; Susanti, I Luh Meiyana Ariss; Wisudayanti, Kadek Heni Oktarina (The Art of Teaching English as a Foreign Language (TATEFL), 2023)
This study aims to examine the effect of using Movie learning media on students’ speaking skills. The research design used in this study was Post-Test Only Control Group Design. The population in this study was the tenth-grade students of SMK TI BALI GLOBAL SINGARAJA with the sample of 25 students collected by using Cluster Random Sampling. Fifteen students of X PPLG class were assigned as the experimental group taught by using Movie learning media, and ten students of X TJKT class as the control group taught without using Movie learning media. The data were analyzed by using descriptive statistics analysis and inferential statistics analysis. The result showed that, in control group, the students’ mean score is 79.96, the standard deviation is 3.409, the maximum score is 86 the minimum score is 76. In experiment group, the students’ mean score is 85.12, the standard deviation is 3.479, the maximum score is 90, the minimum score is 79. The outcomes demonstrated that Movie learning media is statistically very significant and quite effective in student speaking skills. This study found that the use of Movie learning media is effective in teaching speaking. Therefore, teachers are advised to use this media when speaking so that students can easily learn and also have more opportunities to practice and develop their speaking skills.